Anther culture of Glycine max (Merr.): Effect of media on callus induction and organogenesis - Hai, N.H.; Lal, S.K.; Singh, S.K.; Talukdar, A.; 1, Vinod (The Indian Journal of Genetics and Plant Breeding, 2016)
The present study was undertaken to standardize the doubled haploid regeneration protocol for soybean. Studies on association between floral bud size and pollen developmental stage revealed that the bud size of 2.5-4 mm containing microspore at uni-nucleate stage was most responsive for callus induction and organogenesis. Effect of different media on callus induction and plant regeneration in anther culture of three genotypes, namely, JS 335, SL 958 and SL 688 were studied. Combination of 10.0 mg l–12, 4-D and 0.5 mg l–1 BAP supplemented with 90 g l–1 sucrose and 10% v/v of coconut water in B5 medium was found best for callus induction (64.11%). Murashige and Skoog medium supplemented with 2.0 mg l–1 BAP + 1.0 mg l–1 thidiazuron gave shoot bud-like structures, in contrast, B5 medium promoted only root organogenesis (3.30-10.90%). Anther derived callus was confirmed through flow cytometry and root tip cell of anther callus derived roots to be haploid through root tip staining (chromosome number n = 20)